Endoscopic ultrasound with submucosal saline injection improves the accuracy of T1a and T1b staging in superficial esophageal squamous cell carcinoma - Zhang, Jianjun; Chen, Ming; Gao, Yongsheng; Liu, Jinqi; Li, Zengjun; Wang, Dongyang (Frontiers in Medicine, 2025)
BackgroundEndoscopic ultrasound (EUS) is important for diagnosing and staging esophageal cancer. However, substantial variability in the diagnostic and staging accuracy of EUS, especially in early-stage cancers, affects patients’ treatment choices and quality of life.AimsTo explore whether conventional endoscopic ultrasonography (EUS-C) combined with submucosal saline injection (EUS-SSI) improves diagnostic accuracy in preoperative T1a and T1b staging in superficial esophageal squamous cell carcinoma (SESCC).MethodsPatients with SESCC first underwent EUS-C. Then, they received SSI and underwent a repeat EUS. The diagnostic accuracy of EUS-C and EUS-SSI was evaluated based on the final postoperative pathology results.ResultsA total of 92 patients with endoscopically diagnosed SESCC were included in the study. Postoperative pathology confirmed superficial SESCC in all patients (T1a stage, n = 77; T1b stage, n = 15). EUS-C correctly identified 54 of 77 patients with T1a cancer and nine of 15 patients with T1b cancer, whereas EUS-SSI identified 68 of 77 patients with T1a cancer and 10 of 15 patients with T1b cancer. EUS-SSI was more accurate than EUS-C in diagnosing T1a and T1b stage SESCC (84.8 and 68.5%, respectively).ConclusionEUS-SSI differentiates between T1a and T1b stages of superficial SESCC with better diagnostic accuracy than EUS-C, thereby reducing the rate of over-staging.